ВЛИЯНИЕ ОЖИРЕНИЯ НА КАЧЕСТВО ЖИЗНИ У МУЖЧИН ТРУДОСПОСОБНОГО ВОЗРАСТА С АРТЕРИАЛЬНОЙ ГИПЕРТЕНЗИЕЙ - О. В. Каратаева; Е. И. Панова; Н. С. Цыпленкова; Е. П. Морозова (Архивъ внутренней медицины)
Obesity reduces the quality of life in working age men. The incidence of coronary artery disease, heart failure, obstructive sleep apnea, metabolic syndrome and insulin resistance, as well as prevailing more severe hypertension increase in obese patients. We have considered the main factors affecting deterioration in quality of life in patients with obesity, including signs of myocardial remodeling in obesity and their impact on quality of life